A Life Cycle Assessment of Landfilled Municipal Solid Waste in Argentina The Influence of Waste Composition on Greenhouse Gases Emissions and Other Impacts - Caprile, María Daniela; Ripa, Maddalena (Journal of Environmental Accounting and Management, 2026)
Landfills are still among the most common patterns of waste disposal in the world, in spite of the spreading awareness of their environmental impacts. Besides being one of the main sources of greenhouse gases emission (GHG) in the waste management sector, they are also responsible for human and ecosystem toxicity, eutrophication, photochemical oxydation, not to talk of landscape visual degradation, competition for land use and bad smell. In this paper, an empirical model is used to estimate CO2and other gaseous and liquid emissions from landfilling of mixed MSW. By means of an LCA framework, the business-as-usual scenario (landfilling) of San Miguel city (Buenos Aires) is analyzed as a benchmark case and compared to alternative waste management scenarios (40% waste reduction and 50% pre-sorting). Impact potentials are estimated with reference to 1 kg of wet mixed MSW disposed off in a sanitary landfill with bottom liner, leachate collection and treatment, and gas collection. A Life Cycle Impact Assessment (LCIA) of the landfill was performed based on emissions released over a 100 years time interval after disposal. A special focus was placed on Global Warming Potential of landfilled waste (GWP, kg CO2eq), in order to shed light on the different impacts resulting from inclusion or subtraction of biogenic CO2, most often assumed as global warming neutral in published studies. Our results show that: (1) waste composition plays a critical role on waste LCIA; (2) the default exclusion of biogenic CO2emissions can lead to an underestimate of the environmental load of the landfill as far as climate change impact is concerned; (3) global warming, eutrophication, human toxicity and photochemical oxidation are the main impacts of landfilling practices; (4) alternative, waste-prevention and pre-sorting scenarios are likely to decrease such impacts by 20-30% compared to business-as-usual, depending on the investigatedimpact category.